FeO0.7F1.3/C Nanocomposite as a High‐Capacity Cathode Material for Sodium‐Ion Batteries. (20th November 2014) - Zhou, Yong‐Ning; Sina, Mahsa; Pereira, Nathalie; Yu, Xiqian; Amatucci, Glenn G.; Yang, Xiao‐Qing; Cosandey, Frederic; Nam, Kyung‐Wan
<x xml:space="preserve">Abstract</x> Searching high capacity cathode materials is one of the most important fields of the research and development of sodium‐ion batteries (SIBs). Here, we report a FeO0.7F1.3/C nanocomposite synthesized via a solution process as a new cathode material for SIBs. This material exhibits a high initial discharge capacity of 496 mAh g−1 in a sodium cell at 50 °C. From the 3rd to 50th cycle, the capacity fading is only 0.14% per cycle (from 388 mAh g−1 at 3rd the cycle to 360 mAh g−1 at the 50th cycle), demonstrating superior cyclability. A high energy density of 650 Wh kg−1 is obtained at the material level. The reaction mechanism studies of FeO0.7F1.3/C with sodium show a hybridized mechanism of both intercalation and conversion reaction.